Dendrobium jizhuyeense (Orchidaceae; Epidendroideae) a new species from China: evidence from morphology and DNA - Liang, Meng; Chang, Ling-Ling; Wang, Jia-Xin; Zhang , Yu; Liu, Lei; Zhang, Ze; Li, Zhenjian (Phytotaxa, 2024)
Dendrobium jizhuyeense, a new species from Sichuan, China, is described and illustrated in this study. Morphological study indicates that D. jizhuyeense is similar to D. hancockii, but differs in having oblong sepals, obovate-elliptic petals and an obovate lip, including a smaller stem, smaller leaf and different flower type. Molecular analyses based on nuclear and plastid markers indicate that D. jizhuyeense is closely related to D. hancockii, belonging to section Holochrysa.